Domestic violence and the Portuguese justice system from the perspective of professionals from support institutions - Fátima Ney Matos (2022)
In the last decades, the number of cases of domestic violence made public has had a great visibility, which forced the State and Portuguese society to create social responses willing to help and accompany the victims of this type of violence. This work aims to understand the perception that professionals from institutions supporting victims of domestic violence have of the performance of justice in Portugal. Based on a qualitative approach, semi-structured interviews were conducted with managers or those responsible for social responses to victims of domestic violence. The insertion of participants was made for accessibility and intentionality, the “snowball” strategy was also used, in which a participant points out others who have characteristics of interest in the research. Study participants were managers or responsible for social responses to victims of domestic violence, such as support offices for victims of domestic violence in the state or the third sector, and temporary shelter responses for victims. All participants signed the Free and Informed Consent Term to carry out the interviews and the study obtained a favorable opinion from the Institution's Ethics Committee, which it considered to be in accordance with the principles established in the Declaration of Helsinki. The results point to the lack of application of measures capable of maintaining the victim's safety and to a penalty that is too light for a public crime. Although Portuguese legislation has had a very positive evolution in recent decades, the technicians of the victim support institutions interviewed consider Portuguese justice still too lenient in relation to the crime of domestic violence against women.